2017
DOI: 10.4236/ojog.2017.78081
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy after Open Abdominal Surgery with Self-Retaining Retractors. A Systematic Review of Randomised and Non-Randomised Clinical Trials

Abstract: Objectives: A systematic review was undertaken to evaluate the effectiveness of incision retention available to surgeons conducting open abdominal or pelvic surgeries. Both the ability of the retractor to retain the wound and harm to the patient due to the retractor were reviewed. Methods: A search was conducted using the following databases: EMBASE, PubMed, BIOSIS, Engineering Village, Web of Science, Best practice, Science Direct, CRCnet BASE, Proquest, Wiley Online Library, and Comprehensive Biomaterial. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…We could switch intravenous analgesia to oral intake without the need of opioids with good pain control; this outcome may be attributed by thoracic epidural anesthesia. However we think that the O-ring wound retractor also contributed in pain control, supporting us with Lohsiriwat and Chowdary findings in which they concluded reduction in early postoperative pain and a significant reduction in the amount of intravenous analgesia with the use of an O-ring wound retractor in abdominal surgery [3,6]. The patient was discharged home when the pain was well controlled with oral pain medications (3 days).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We could switch intravenous analgesia to oral intake without the need of opioids with good pain control; this outcome may be attributed by thoracic epidural anesthesia. However we think that the O-ring wound retractor also contributed in pain control, supporting us with Lohsiriwat and Chowdary findings in which they concluded reduction in early postoperative pain and a significant reduction in the amount of intravenous analgesia with the use of an O-ring wound retractor in abdominal surgery [3,6]. The patient was discharged home when the pain was well controlled with oral pain medications (3 days).…”
Section: Discussionsupporting
confidence: 79%
“…Lohsiriwat in 2014 identified soft tissue damage as a comorbid factor that intensifies post-operative pain and cause cicatrisation outcome alteration [3,4]. In 2012 Cheng and Biewenga reported that atraumatic O-ring retractor is a modern self-retaining wound retractor which provides circumferential retraction that causes less tissue damage, thus reducing pain following open surgeries than conventional auto self-retractors [4][5][6]. Modified Ravitch procedure has been associated to soft tissue complications due extensive dissection and prolonged intravenous analgesia administration for pain management [1,2].…”
Section: Introductionmentioning
confidence: 99%